Functions of the press: Analysis of content - Test of local radio 1973 - Weibull, Lennart; Aldemark, Lars; Strid, Jan (University of Gothenburg, 1982)
This study is part of the research program The Role of the Press in Society, a project initiated by the 1972 Commission of tbe Press. The survey illustrates how companies regard their relation to the local area, to the general public and member and which part various types of media plays in the work of the enterprise. Further some questions were put about which role the daily press should have in political life.

This study is part of the research program The Role of the Press in Society, a project initiated by the 1972 Commission of tbe Press. The survey illustrates how companies regard their relation to the local area, to the general public and member and which part various types of media plays in the work of the enterprise. Further some questions were put about which role the daily press should have in political life.
Pressens funktioner: Innehållsanalysen - Lokalradioförsöket 1973
Keywords: Media; Media; Social Sciences; Samhällsvetenskap